Pengaruh Sektor Pariwisata terhadap Pendapatan Asli Daerah Kabupaten/Kota di Provinsi Bali - Ida Ayu Nyoman Sri Rahayu; Ni Ketut Budiningsih (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Local Revenue (PAD) reflects a region’s ability to generate and manage its own sources of income to support regional development. The tourism sector is closely related to PAD, as tourism activities stimulate economic transactions that become objects of local taxation. This study aims to analyze the effect of the number of domestic tourist trips, the number of restaurants, the number of hotels, and the number of international tourists on PAD. The study covers all regencies/cities in Bali Province over the period 2020–2024. The analytical technique employed is panel data regression with a total of 45 observations. The results indicate that, partially, only the number of domestic tourist trips has a positive and significant effect on PAD. Meanwhile, the number of hotels has a significant negative effect, whereas the number of restaurants and the number of international tourists do not have a significant effect on PAD in the regencies/cities of Bali Province. However, simultaneously, all independent variables, the number of domestic tourist trips, the number of restaurants, the number of hotels, and the number of international tourists, have a significant effect on PAD.